Program Pendampingan Balita Gizi Kurang di Desa Mlokomanis Wetan, Kabupaten Wownogiri - Ahmad Sulaeman; Sarwititi Sarwoprasodjo; Rinanda Dwi Saputri; Larasati Khairunnisa (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2020)
Toddler nutritional status is an important thing to note because toddlers are a stage of life which is an important point of physical and cognitive growth of children, including the first 1000 days of life (1000 HPK). Based on Data on Toddler Nutrition Status in UPTD Ngadirojo Public Health Center, there are 102 toddlers who have undernourished status and 10 of them are in Mlokomanis Wetan Village. Seeing these problems it is felt necessary to create a program that can increase the weight of toddlers who have underweight nutritional status and also improve the knowledge of toddlers' parents about PMT (Supplementary Feeding), diverse foods, and PHBS (Clean and Healthy Behavior) that affect toddler growth and development. The target of this program is four mothers and toddlers with poor nutritional status in Mlokomanis Wetan Village. The activity was carried out through visits which were carried out four times in a period of four weeks. Most of the children under five with poor nutritional status still have diets that are not yet diverse, as well as under-five mothers' knowledge regarding nutrition that is still lacking. Based on the measurement results, only two toddlers who gained weight during the four weeks of the mentoring process. Based on the results of 1x24 hour recall conducted on the second visit, most toddlers still consume foods that are not yet diverse and also environmental hygiene that has not been maintained. The program can be declared successful by using indicators of success in the form of an increase seen from anthropometric measurements. although it is necessary to provide continuous assistance until the nutritional status of children under five returns to normal. Keywords: clean and healthy lifestyle, Mlokomanis Wetan Village, provision of supplementary food, toddler nutrition status